District Heating System: Interactive Website Project for Weilheim, Germany - Feigl, Anita; Utesch, Matthias (International Journal of Engineering Pedagogy (iJEP), 2024)
District heating systems play a crucial role in the European Union for sustainable energy practices by contributing to reducing carbon emissions and thus counteracting climate change. In most European countries, the energy consumption for heating is a topic that needs to be considered. Germany has recognized the need for more awareness among its citizens about district heating systems. Therefore, an interactive website was developed in close cooperation with the city of Weilheim in Bavaria, Germany. The goal is to inform citizens about the district heating system under construction. The website aims to improve user engagement through interactive features, including a quiz, an interactive calculator, and various animations and images. The application focuses on the primary energy sources biomethane, solar energy, wood chips, and the use of environmental heat through heat pumps. The website was evaluated at a local secondary school, which yielded positive feedback.